Produktivitas Lansia di Karangwredha Puntodewo Kelurahan Tanggung Kecamatan Kepanjen Kidul Kota Blitar - Yusup Asrori (Journal of Ners and Midwifery, 2014)
Productivity Elderly elderly is still capable of doing the job or activity that can make money, goods or services. The purpose of the study was to describe the productivity of the elderly in the Village Puntodewo Karangwerda Kepanjenkidul Blitar District of Responsibility. Method: Research design was Â descriptive design. The population in this study is all elderly in Karangwerda Puntodewo Kelruhan Kepanjenkidul Blitar District of Responsibility. Research samples was 55 elderly. Data collection was conducted by questionnaire at May 22nd until May 31th, 2014.. Result: The Results showed that from 55 elderly, 29,1%work and 10,9% elderly does not work. Agriculture and trade become the foundation of elderly workers. The average of Â salary received by elderly month work at Rp 552 181, -. Income derived mostly from the elderly to use the money for everyday needs such as eating, drinking, capital of the store, working the fields, giving pocket for grandchildren as much as 67% . While seniors who use the money for the benefit of such family and save for medical expenses at any time if the pain was 33% .